The World Federation of ADHD International Consensus Statement: 208 Evidence-based conclusions about the disorder. (September 2021) - Faraone, Stephen V.; Banaschewski, Tobias; Coghill, David; Zheng, Yi; Biederman, Joseph; Bellgrove, Mark A.; Newcorn, Jeffrey H.; Gignac, Martin; Al Saud, Nouf M.; Manor, Iris; Rohde, Luis Augusto; Yang, Li; et al.
Highlights: ADHD occurs in 5.9 % of youth and 2.5 % of adults. Most cases of ADHD are caused by the combined effects of many genetic and environmental risks. There are small differences in the brain between people with and without ADHD. Untreated ADHD can lead to many adverse outcomes. ADHD costs society hundreds of billions of dollars each year, worldwide. Abstract: Background: Misconceptions about ADHD stigmatize affected people, reduce credibility of providers, and prevent/delay treatment. To challenge misconceptions, we curated findings with strong evidence base. Methods: We reviewed studies with more than 2000 participants or meta-analyses from five or more studies or 2000 or more participants. We excluded meta-analyses that did not assess publication bias, except for meta-analyses of prevalence. For network meta-analyses we required comparison adjusted funnel plots. We excluded treatment studies with waiting-list or treatment as usual controls. From this literature, we extracted evidence-based assertions about the disorder. Results: We generated 208 empirically supported statements about ADHD. The status of the included statements as empirically supported is approved by 80 authors from 27 countries and 6 continents. The contents of the manuscript are endorsed by 366 people who have read this document and agree with its contents. Conclusions: Many findings in ADHD are supported by meta-analysis. These allow for firm statements about the nature, course, outcome causes, and treatments for disorders that are useful for reducing misconceptions and stigma.